Numerical analysis of the thermal performance of vapour compression heat pump heat exchanger using Python and computational fluids dynamics (CFD) - Sehobai, Sehobai Elliot (Department of Mechanical Engineering, 2025)
Numerical analysis on fin and tube heat exchangers contributes towards the implementation of energy-efficient technologies in the industrial and building sectors. Fin and tube heat exchangers are found in various mechanical applications including heating, ventilation, and air conditioning (HVAC) and refrigeration systems, the oil and gas extraction industry, power plants and many more. Due to the rapid depletion of energy resources worldwide, there is a need to reduce energy consumption, especially for systems that use electricity such as heat pump systems. This led to several studies on the heat exchangers used in heat pumps including analyses of the heat exchanger geometry and working fluid impacts on the thermal performance. This study describes numerical analyses on the fin and tube heat exchanger model developed in Python, using nonuniform airflow velocities calculated in Ansys Fluent. The geometrical parameters of the modelled heat exchanger are based on the literature values. The heat transfer rates, pressure losses, vapour quality and all refrigerant properties are calculated by discretizing each tube on each tube circuit and tube row into several increments and incorporating nonuniform airflow in three dimensional. The model is validated using experimental data which shows that the maximum variation between the model and experimental results is less than 10.0%. The velocity contours from the Ansys Fluent heat exchanger model suggest that airflow varies significantly in three dimensional. The results from the modelled heat exchanger in Python show that the nonuniformity of airflow consequently affects the refrigerant pressure losses, heat transfer and vapour quality in the refrigerant tubes. Thus, assuming uniform airflow over the heat exchanger results in underestimating the actual refrigerant pressure losses, heat transfer and vapour quality in the upper refrigerant tube circuits (those located closer to the top of the heat exchanger) while overestimating these parameters on lower tube circuits (those located towards the bottom, farther from the fan location). This leads to a maximum variation exceeding 10.0%. Moreover, the coefficient of performance (COP) was also calculated from the heap pump model developed in Python. These model results suggest that generally, assuming uniform airflow on the heat exchanger underpredicts the heat pump COP by a maximum variation of 11,07% for all four operating conditions of the heat pump discussed in this study. These results highlight the importance of performing analysis in three-dimensional space, considering non uniform airflow.